2021
DOI: 10.1111/rec.13432
|View full text |Cite
|
Sign up to set email alerts
|

Marine ecosystem restoration in a changing ocean

Abstract: Multiple human impacts on natural ecosystems cause ongoing widespread habitat loss, with consequent decline of biodiversity and ecosystem services. Seas and oceans, the largest biomes of the biosphere, show increasing numbers of degraded habitats. Ecological restoration offers a major tool to reverse this trend and recover biodiversity, along with human health and wellbeing. The United Nations Decade on Ecosystem Restoration promotes global-scale restoration of degraded habitats and we can exploit lessons lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 63 publications
(71 reference statements)
0
13
0
Order By: Relevance
“…Despite its late start compared to restoration on land, marine restoration holds enormous potential as an important tool for developing strategies to ensure that the oceans continue to provide the goods and services on which the well-being of life on Earth depends (Danovaro et al, 2021). The results of this study suggest that outplanting of infralittoral canopy-forming species such as G. barbata in the northern Adriatic should be further tested and improved, at least on the Slovenian coasts of the Gulf of Trieste.…”
Section: B a Figurementioning
confidence: 96%
“…Despite its late start compared to restoration on land, marine restoration holds enormous potential as an important tool for developing strategies to ensure that the oceans continue to provide the goods and services on which the well-being of life on Earth depends (Danovaro et al, 2021). The results of this study suggest that outplanting of infralittoral canopy-forming species such as G. barbata in the northern Adriatic should be further tested and improved, at least on the Slovenian coasts of the Gulf of Trieste.…”
Section: B a Figurementioning
confidence: 96%
“…We suggest that future research investigate not only the pathogenicity of the viruses we have identified (and others yet to be discovered), but also their interactions with anthropogenic stressors. Should such links be identified, the solutions are likely to require an “one health” mindset in which particular environmental drivers are identified and acted upon with the expectation of multiple benefits (Danovaro et al 2021 ; Schweizer et al 2022 ). Ecosystem-level improvements to water quality, for example, would likely have broad benefits beyond safeguarding bonefish health, ideally leading to improved human health and ecosystem integrity.…”
Section: Discussionmentioning
confidence: 99%
“…The recovery of degraded or damaged habitats represents a crucial aid for management strategies to provide biodiversity conservation and improving services for human health and well-being (Possingham et al, 2015). However, active marine habitat restoration has extremely high costs (Bayraktarov et al, 2016) that in deep habitats are estimated to rise by two or three orders of magnitude per hectare if compared to the costs of activities carried out in coastal marine ecosystems (Van Dover et al, 2014;Danovaro et al, 2021;Montseny et al, 2021). The potential of recovery actions, proven by positive outcomes of worldwide efforts carried out both on land and underwater, together with the need to reverse the trend of ecosystems degradation, are the pillars of the UN Decade on Ecosystem Restoration 2021-2030: a global rallying cry to heal our planet (https://www.decadeonrestoration.org/).…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative impact assessment studies on key taxa or ecosystems have dramatically updated information for the Mediterranean Sea, where up to the 99% of the territorial waters of EU member states are subjected to high impact, and less than 1% of the surface is relatively unaffected by human activities (Micheli et al, 2013;Gerovasileiou et al, 2019). The effects of the multiple drivers that lead to the degradation of habitats within the European seas will increase in the next few decades without a sustainable approach to using natural resources, large-scale actions to mitigate human impacts through ecosystem-based management, and effective restoration programs (Danovaro et al, 2021).…”
Section: Introductionmentioning
confidence: 99%